A newly updated and annotated checklist of the Anthocerotae and Hepaticae of Qinling Mts., China. (1st October 2016) - Jia, Yu; He, Qiang; Li, Feng-Xia; He, Si; Wang, Mei-Zhi; Wu, Peng-Cheng
Abstract : An updated checklist of the Anthocerotae and Hepaticae for Qinling (Mts.) recognizes 261 species, 20 varieties, 9 subspecies and 2 forms in 86 genera and 44 families. The distributional ranges are provided for each taxon in Qinling. The information in this paper is based on a review of the previous reports up to 2014 and the specimens held in PE, KUN, HSNU, SDNU, WUK and WNU herbaria. Eight genera, 122 species, 6 varieties and 6 subspecies are new records for Qinling, including two taxa newly recorded for China. Fifteen species, 8 varieties, and 2 forms are endemic to China.